Fear and safety learning differentially affect synapse size and dendritic translation in the lateral amygdala - Ostroff, Linnaea E. (National Academy of Sciences, 2010)
Fear learning is associated with changes in synapse strength in the lateral amygdala (LA). To examine changes in LA dendritic spine structure with learning, we used serial electron microscopy to re-construct dendrites after either fear or safety conditioning. The spine apparatus, a smooth endoplasmic reticulum (sER) specialization found in very large spines, appeared more frequently after fear conditioning. Fear conditioning was associated with larger synapses on spines that did not contain a spine apparatus, whereas safety conditioning resulted in smaller synapses on these spines. Synapses on spines with a spine apparatus were smaller after safety conditioning but unchanged with fear conditioning, suggesting a ceiling effect. There were more polyribosomes and multivesicular bodies throughout the dendrites from fear conditioned rats, indicating increases in both protein synthesis and degradation. Polyribosomes were associated with the spine apparatus under both training conditions. We conclude that LA synapse size changes bidirectionally with learning and that the spine apparatus has a central role in regulating synapse size and local translation.